Microstructural refinement and corrosion resistance improvement of heat-treated A356 alloy processed by equal channel angular pressing - Gebril, M.A.; M.Z. Omar,; N.K. Othman,; I.F. Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The microstructure refinement, hardness and corrosion resistance of heat-treated A356 aluminium alloy processed by equal-channel angular pressing (ECAP) were investigated. ECAP was carried out at room temperature using a mold, with a channel angle of 120° via route A. Results of the investigation confirm that the flaky coarse silicon particles were effectively fragmented from 4.22 to 0.761 μm and the grain size reduced from 171 to 40 μm after four passes of heat-treated as-cast using ECAP process. ECAP processing increases the hardness of heat-treated as-cast alloy from 61 Hv to 125 HV after four passes. Heat-treated A356 alloy shows enhanced corrosion resistance from 0.0424 to 0.00149 mmy-1, after four passes. In this research, ECAP processing has been shown to improve the hardness and corrosion resistance of as-cast A356 alloy.